Circular Economy-Based Coffee Development Strategy in Bangka Belitung: Reducing Waste and Enhancing Added Value - Raden Achmad Djazuli; Sekar Tanjung, Garist (Fakultas Ekonomi dan Bisnis, Universitas Bangka Belitung, 2025)
This research examines the implementation of circular economy principles in the coffee agribusiness value chain in Bangka Belitung Islands Province. Using a qualitative approach based on secondary data, this study conducts an in-depth analysis of policy documents, technical reports, scientific publications, and documented case studies. Through thematic and ecological economics analysis techniques, the research identifies the potential for transforming coffee waste into value-added products within a circular economy framework. The results show that utilizing coffee husks as organic fertilizer, animal feed, and raw materials for creative industries has the potential to create additional economic value of 38–45% of the main product value, while reducing negative environmental externalities by 65%. A pentahelix-based development model (academia, business, community, government, and media) with a transdisciplinary approach is key to the successful implementation of the circular economy in the study area. Systemic interventions in institutional, technological, policy, and market aspects are needed to accelerate the transition toward an inclusive and sustainable circular economy. This research provides theoretical contributions to the development of circular economy models based on tropical commodities as well as practical implications for formulating sustainable development policies in post-mining island regions.